Calculating catastrophe - Woo, Gordon (Imperial College Press, 2011)
Explains the underlying quantitative basis for understanding catastrophe phenomena, both natural and man-made. In this book, the catastrophes covered range from geological, meteorological and hydrological hazards to political violence, industrial, ecological and financial risk